A systematic review of infant feeding experience and hospitalisation in developed countries. (5th December 2013) - Williams, Lesley A; Davies, Peter SW; Boyd, Roslyn; David, Michael; Ware, Robert S
Abstract The review examines whether mode of feeding is associated with risk of hospitalisation for illness during infancy in developed countries. Databases were searched for published studies that included the terms 'infant feeding' and 'hospitalisation'. Six studies were included. Breastfeeding was associated with a reduced risk of hospitalisation and adjusted analyses showed mixed results. Conclusion There is no clear relationship between mode of feeding and reduction of infant hospitalisation for illness in developed countries.